Ni Paste and its Uses

JP7943982B1Active Publication Date: 2026-10-30NORITAKE MACHINE TECHNO CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2026123756
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-30
Estimated Expiration
2046-07-01

AI Technical Summary

Benefits of technology

【0010】 ここで開示される技術によると、Niペーストが開示される。このNiペーストは、無機成分と、バインダ樹脂と、分散剤と、有機溶剤とを含む。無機成分は、ニッケル粉末と誘電体粉末とを含む。分散剤は、以下の式(X): 【化】 (式中、R1は、炭素数が10~20の鎖状炭化水素基である。) で示される第1分散剤と、ポリエーテル酸および/またはポリカルボン酸である第2分散剤と、アルキルアミンである第3分散剤とを含む。Niペーストにおける第1分散剤は、無機成分の総表面積(m2)に対して少なくとも0.45mgある。第2分散剤のアミン価と第3分散剤のアミン価との合計値ATと、第2分散剤の酸価と第3分散剤の酸価との合計値CTとの比(AT/CT)は、1.11~7.50である。分散剤の合計量は、無機成分の総表面積(m2)に対して、少なくとも1.40mgある。かかる構成によると、ニッケル粉末と誘電体粉末との分散性を高めることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943982000010
    Figure 0007943982000010
  • Figure 0007943982000011
    Figure 0007943982000011
  • Figure 0007943982000012
    Figure 0007943982000012
Patent Text Reader

Abstract

Providing a technique for improving the dispersibility of nickel powder and dielectric powder in Ni paste [Solution] The Ni paste disclosed herein includes an inorganic component, a binder resin, a dispersant, and an organic solvent. The inorganic component includes nickel powder and dielectric powder. The dispersant is represented by the following formula (X): 【Chemical Formula 1】 TIFF0007943982000009.tif26170 (wherein R1 is a chain hydrocarbon group having 10 to 20 carbon atoms.) a first dispersant represented by the formula, a second dispersant which is a polyether acid and / or a polycarboxylic acid, and a third dispersant which is an alkylamine. The first dispersant in the Ni paste is at least 0.45 mg relative to the total surface area (m 2 ) of the inorganic component. The total value A of the amine value of the second dispersant and the amine value of the third dispersant T and the total value C of the acid value of the second dispersant and the acid value of the third dispersant T the ratio (A T / C T ) is 1.11 to 7.50. The total amount of the dispersant is at least 1.40 mg relative to the total surface area (m 2 ) of the inorganic component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to Ni paste and its uses. [Background technology]

[0002] Multilayer ceramic capacitors (MLCCs) are used in a variety of electronic devices due to their small size and high capacitance. An MLCC has a structure in which multiple dielectric layers containing a dielectric (ceramic material) and internal electrode layers containing a conductive metal are stacked. In the manufacturing of MLCCs, a conductive paste containing conductive particles is applied to the surface of a green sheet (dielectric sheet) containing the dielectric. After drying, the layers are stacked, compressed, cut, and then fired. In this simultaneous firing process, the conductive paste tends to shrink more quickly than the dielectric sheet. This difference in thermal shrinkage behavior can cause, for example, poor contact or delamination between the internal electrode layer and the dielectric layer. Therefore, dielectric particles are added to the conductive paste used for MLCCs. This allows the thermal shrinkage behavior of the dielectric sheet and the conductive paste to be approximated.

[0003] Japanese Patent Publication No. 2025-81376 discloses a conductive paste comprising conductive powder, ceramic powder, a dispersant, a binder resin, and an organic solvent. The dispersant comprises an amino acid-based dispersant represented by a predetermined chemical formula in an amount of 0.01 parts by mass to 4 parts by mass per 100 parts by mass of conductive powder, and an amine-based dispersant represented by a predetermined chemical formula in an amount of 0.01 parts by mass to 4 parts by mass per 100 parts by mass of conductive powder. The publication states that this configuration reduces the number of minute protrusions that form on the dried film after printing.

[0004] Japanese Patent No. 4238575 discloses a conductive paste for internal electrodes of a multilayer ceramic capacitor. The conductive paste contains at least conductive metal particles, a co-material, a resin, an organic solvent, and an organic additive. The co-material consists of the main constituent materials of the green sheet. The resin contains at least polyvinyl butyral. The organic additive (excluding phosphate ester type surfactants) is a compound having a functional group exhibiting an acid value and a functional group exhibiting an amine value, or / or a mixture of a compound having a functional group exhibiting an acid value and a compound having a functional group exhibiting an amine value. The ratio of the acid value to the amine value of the organic additive (amine value / acid value) is 0.2 to 5.0. The amount of organic additive in the paste is 0.001 to 5.0% by weight. The publication states that this configuration can improve the crush strength and electrode alignment of the multilayer chip, and can improve the adhesion between the electrode dry film and the upper dielectric green sheet.

[0005] Japanese Patent Publication No. 6791194 discloses a paste for internal electrodes of a multilayer ceramic capacitor containing nickel powder, a vehicle, a dispersant, and dielectric powder. This paste satisfies a predetermined relationship when the acid value of the organic compounds X1, X2, ..., Xn (n is a natural number of 1 or more) constituting the dispersant is Xi-ac, the amine value of the organic compounds is Xi-am, and the amount of parts by mass of the organic compounds per 100 parts by mass of nickel powder is wi (i=1~n). The total amount of dispersant (Σwi) is 2.0 parts by mass or less per 100 parts by mass of nickel powder. At least one of a viscosity modifier, a flame retardant, or a settling inhibitor is added. The publication states that with this configuration, a high conductive film density can be obtained even in a conductive film containing conductive powder with adsorbed dispersant.

[0006] Japanese Patent Publication No. 7279643 discloses a conductive paste comprising a conductive powder, a dispersant, a binder resin, and an organic solvent. The dispersant comprises a first acidic dispersant and a second acidic dispersant. The first acidic dispersant is an alkyl phosphate compound. The second acidic dispersant is an acidic dispersant having a carboxyl group, other than the first acidic dispersant. The binder resin comprises an acetal resin. The organic solvent comprises a glycol ether solvent. The alkyl phosphate compound has a predetermined chemical structure. The publication states that this configuration provides a paste having viscosity suitable for gravure printing and excellent dispersibility and productivity. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2025-81376 [Patent Document 2] Patent No. 4238575 [Patent Document 3] Patent No. 6791194 [Patent Document 4] Patent No. 7279643 [Overview of the project] [Problems that the invention aims to solve]

[0008] Incidentally, in recent years, there has been a demand for further miniaturization of electronic components such as MLCCs. For example, in miniaturizing MLCCs, it is necessary to thin the internal electrodes. Accordingly, the conductive powder (e.g., nickel powder) and co-material powder (dielectric powder) contained in the conductive paste are tending to become smaller in particle size. With this trend, it is required that the particles constituting the powder be dispersed more highly in the conductive paste.

[0009] The technology disclosed herein has been made in view of the circumstances described above, and its main purpose is to provide a technology for improving the dispersibility of nickel powder and dielectric powder in Ni paste. [Means for solving the problem]

[0010] The technology disclosed herein discloses a Ni paste. This Ni paste comprises an inorganic component, a binder resin, a dispersant, and an organic solvent. The inorganic component comprises nickel powder and dielectric powder. The dispersant is given by the following formula (X): [ka] (In the formula, R1 is a chain-like hydrocarbon group having 10 to 20 carbon atoms.) The first dispersant is represented by , the second dispersant is a polyether acid and / or polycarboxylic acid, and the third dispersant is an alkylamine. In Ni paste, the first dispersant is the total surface area (m²) of the inorganic components. 2 ) contains at least 0.45 mg. The sum of the amine values ​​of the second dispersant and the third dispersant is A. T The sum of the acid values ​​of the second dispersant and the third dispersant, C. T The ratio (A T / C T The ratio is 1.11 to 7.50. The total amount of dispersant is the total surface area (m²) of the inorganic components. 2 There is at least 1.40 mg of this. With this configuration, the dispersibility between nickel powder and dielectric powder can be improved.

[0011] From another perspective, the technology disclosed herein provides a method for manufacturing electronic components. This manufacturing method includes forming a coating film of the aforementioned Ni paste on a substrate surface and heat-treating the substrate and the coating film to obtain a fired coating film. In the aforementioned Ni paste, the dispersibility of nickel powder and dielectric powder is enhanced. Therefore, this manufacturing method makes it possible to manufacture electronic components containing a uniform fired Ni paste film. [Brief explanation of the drawing]

[0012] [Figure 1] Figure 1 is a schematic cross-sectional view of MLCC1. [Figure 2] Figure 2 shows an example of a successful separation evaluation in a test case. [Figure 3] Figure 3 shows an example of a failed separation evaluation in a test case. [Modes for carrying out the invention]

[0013] The embodiments of the technology disclosed herein will be described below. Matters other than those specifically mentioned herein that are necessary for carrying out the technology disclosed herein can be understood based on the technical content taught herein and the common technical knowledge of those skilled in the art. The technology disclosed herein can be carried out based on the content disclosed herein and the common technical knowledge of the art. In this specification and in the claims, A to B (where A and B are arbitrary numbers) means A or greater and B or less, and also includes the case where A is greater and B is less than or equal to A.

[0014] In this specification, "fired film" refers to a film-like material in which organic components (e.g., dispersants; organic solvents; additives such as binder resins, etc.) in the Ni paste are removed by heat treatment (firing treatment), and inorganic components (e.g., Ni particles; dielectric particles such as barium titanate particles; other inorganic particles) are sintered. The "fired film" includes an "electrode layer." The electrode layer includes wiring (linear bodies), wiring patterns, and solid patterns. In this specification, "coating film" includes an unfired (pre-firing) film-like material. Therefore, the coating film contains organic components. The coating film includes a dried film obtained by subjecting the Ni paste applied to the substrate to a drying treatment.

[0015] The Ni paste disclosed herein comprises an inorganic component, a binder resin, a dispersant, and an organic solvent.

[0016] The inorganic component is a component that imparts functionality to a fired film obtained by subjecting a coating film of Ni paste to heat treatment. The inorganic component includes nickel powder and dielectric powder.

[0017] The nickel powder is a component that imparts electrical conductivity to the fired film of the Ni paste. The nickel powder may contain inevitable impurities generated in the production process of the powder in an amount of approximately 2 mass% or less (preferably 1 mass% or less, more preferably 0.5 mass% or less) of the entire powder. The nickel powder can be constituted of, for example, particles made of a simple substance of nickel (Ni), or particles made of an alloy containing nickel. As used herein, the alloy containing nickel is an alloy in which the content ratio of nickel in the whole is approximately 40 mass% or more, for example 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more, still more preferably 80 mass% or more, particularly preferably 90 mass% or more, and less than 100 mass%, or 98 mass% or less. Examples of such an alloy include nickel-copper (Ni-Cu), nickel-aluminum (Ni-Al) and the like. The alloy containing nickel is preferably an alloy whose main component is nickel. In the present specification, "P is the main component of Q" means that among the components constituting Q, P is the component having the maximum content relative to the entire Q. Alternatively, the nickel powder may be core-shell particles having nickel particles as a core (for example, particles in which the surfaces of nickel particles are coated with a noble metal such as silver).

[0018] The BET specific surface area of the nickel powder is not particularly limited, and can be set as appropriate. As the BET specific surface area increases, for example, a thinner dried film can be stably formed. From such a viewpoint, the BET specific surface area of the nickel powder is, for example, 0.1 m 2 / g or more, 0.5 m 2 / g or more is preferable, 1 m 2 / g or more is more preferable, 1.5 m 2A BET specific surface area of ​​10 m² or more is even more preferable. On the other hand, the smaller the BET specific surface area, the lower the surface energy of the nickel particles in Ni paste, for example, and thus the more the aggregation of particles in Ni paste can be suppressed. This makes it possible to achieve a more homogeneous coating film, improve the dispersibility of nickel powder in Ni paste, and improve the storage stability of Ni paste. From this viewpoint, the BET specific surface area of ​​nickel powder is, for example, 10 m². 2 / g or less, 8m 2 Preferably less than / g, 6m 2 It is more preferable that the value be less than or equal to / g. In this specification, "BET specific surface area" refers to the specific surface area calculated by the BET method (e.g., BET single-point method) based on the amount of gas adsorbed by a gas adsorption method (constant volume adsorption method) using nitrogen (N2) gas as the adsorbate.

[0019] Nickel powder BET particle size D BET The particle size is, for example, 0.01 μm to 1 μm, preferably 0.03 μm to 0.8 μm, more preferably 0.05 μm to 0.6 μm, and even more preferably 0.1 μm to 0.5 μm. Here, the BET particle size D of the powder BET This is expressed by the following equation (A): BET particle size D BET =6 / (S·ρ) (A) It can be calculated by using the following formula (A) above. In formula (A) above, "S" is the BET specific surface area (m²) of the powder. 2 It is ( / g). "ρ" is the density of the powder (g / m³). 3 )

[0020] The nickel particles constituting the nickel powder are not particularly limited, but may be spherical, flaky, needle-shaped, irregularly shaped, etc. From the viewpoint of improving the handling and applicability of the Ni paste to the substrate, the nickel particles are preferably spherical. From this viewpoint, the average aspect ratio of the nickel powder is preferably 1 to 1.5. Here, the aspect ratio of the particles is the ratio (b / a) of the length of the long side (b) to the length of the short side (a) of the particle when the nickel particles are observed with a scanning electron microscope (SEM) and a rectangle is drawn circumscribing the obtained observation image. The average aspect ratio of the powder is the arithmetic mean of the aspect ratios of multiple particles (e.g., 100 particles).

[0021] The average particle size of the nickel powder is, for example, 0.01 μm to 1 μm, preferably 0.03 μm to 0.8 μm, more preferably 0.05 μm to 0.6 μm, and even more preferably 0.1 μm to 0.5 μm. In this specification, "average particle size" refers to the particle size that corresponds to the cumulative 50% of the smallest particle size in the particle size distribution based on electron microscope observation.

[0022] From the viewpoint of improving the conductivity of the fired film, when the total inorganic components are considered to be 100% by mass, the nickel powder content is, for example, 55% by mass or more, preferably 60% by mass or more, more preferably 65% ​​by mass or more, and even more preferably 70% by mass or more. On the other hand, from the viewpoint of allowing the dielectric powder described later to exhibit its function more appropriately, when the total inorganic components are considered to be 100% by mass, the nickel powder content is, for example, 98% by mass or less, preferably 97% by mass or less, more preferably 96% by mass or less, and even more preferably 95% by mass or less.

[0023] Dielectric powder is a component that mitigates the thermal shrinkage of nickel powder when the Ni paste coating is heat-treated. Furthermore, dielectric powder can also function as a co-material that improves the sintering bonding between the dielectric layer and the internal electrode layer in the manufacturing process of electronic components (e.g., MLCCs). Dielectric powder may contain unavoidable impurities generated during the manufacturing process of the powder, in amounts of approximately 2% by mass or less (preferably 1% by mass or less, more preferably 0.5% by mass or less) of the total powder.

[0024] The dielectric powder may be, for example, a ceramic powder used in this type of application. Examples of materials for the dielectric powder include metal oxides such as barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, zirconium titanate, zinc titanate, barium magnesium niobate, calcium zirconate, strontium zirconate, calcium strontium titanate zirconate, titanium dioxide (rutile), titanium pentoxide, hafnium oxide, zirconium oxide, aluminum oxide, forsterite, niobium oxide, barium neodymate titanate, and silica. The dielectric powder may consist of a single component or may contain two or more components.

[0025] The BET specific surface area of ​​the dielectric powder is not particularly limited and can be set as appropriate. A larger BET specific surface area allows for, for example, the stable formation of thinner dry films and a reduction in the surface roughness of the dry film. From this viewpoint, the BET specific surface area of ​​the dielectric powder is, for example, 1 m². 2 / g or more, 5m 2 Preferably 10m / g or more, 2 More preferably 15m / g or more, 2 A value of 100 m² or more is even more preferable. On the other hand, the smaller the BET specific surface area, the better the aggregation of particles can be suppressed, for example, thus improving the homogeneity, dispersibility, and storage stability of the Ni paste. From this viewpoint, the BET specific surface area of ​​the dielectric powder is, for example, 100 m². 2 / g or less, 85m 2 Preferably less than / g, 70m 2BET particle size D of dielectric powder is more preferable. BET For example, the wavelength is 1 nm to 200 nm, preferably 3 nm to 75 nm, more preferably 5 μm to 150 nm, and even more preferably 10 μm to 120 nm.

[0026] The particles constituting the dielectric powder are not particularly limited, but may be spherical, flaky, needle-shaped, irregularly shaped, etc.

[0027] The average particle size (SEM diameter) of the dielectric powder is, for example, 1 nm to 200 nm, preferably 3 nm to 150 nm, more preferably 5 nm to 100 nm, and even more preferably 10 nm to 70 nm.

[0028] While not particularly limited, it is preferable that the average particle size D2 of the dielectric powder be smaller than the average particle size D1 of the nickel powder, from the viewpoint of forming an electrode layer with excellent electrical conductivity and improving the homogeneity and density of the electrode layer. The ratio of D1 to D2 (D1 / D2) is, for example, 2 or more, preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. From a similar viewpoint, the ratio of D1 to D2 (D1 / D2) is, for example, 100 or less, preferably 50 or less, and more preferably 25 or less.

[0029] From the viewpoint of better exhibiting the function of the co-material, when the total inorganic components are considered to be 100% by mass, the content of dielectric powder is, for example, 1% by mass or more, preferably 2% by mass or more, and more preferably 3% by mass or more. On the other hand, from the viewpoint of improving the conductivity of the fired film, when the total inorganic components are considered to be 100% by mass, the content of dielectric powder is, for example, 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less.

[0030] The inorganic component may include conductive powders (metal powders) other than nickel powder, as long as they do not significantly impair the effects of the technology disclosed herein. Such conductive powders are not particularly limited, and one or more types from those conventionally known may be used. Examples of conductive powders include elemental base metals such as aluminum (Al), copper (Cu), and tungsten (W); elemental noble metals such as gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), and osmium (Os); and alloys containing any of these. When the inorganic component includes conductive powders other than nickel powder, the content thereof is, for example, 2% by mass or less, and preferably 1% by mass or less, relative to the total Ni paste.

[0031] The binder resin is a component that adjusts the viscosity (fluidity) of the Ni paste and imparts tackiness to the Ni paste coating, thereby ensuring close adhesion between nickel powders and between nickel powders and the substrate. The binder resin is preferably a component that burns away during firing. The decomposition temperature of the binder resin may be lower than the firing temperature of the Ni paste coating, for example, 500°C or lower.

[0032] The type of binder resin is not particularly limited. The binder resin may consist of one or more conventionally known organic compounds used in this type of application, depending on the application of the Ni paste, the type of substrate, etc. Examples of binder resins include organic polymer compounds such as cellulose resins, polyvinyl acetal resins, polyvinyl alcohol resins, acrylic resins, urethane resins, epoxy resins, phenolic resins, rosin resins, polyester resins, and ethylene resins. Among these, it is preferable that the binder resin contains a cellulose resin from the viewpoint of improving the burnability during firing and the surface smoothness of the electrode layer. Alternatively, it is preferable that the binder resin contains a polyvinyl acetal resin from the viewpoint of improving the integrity of the Ni paste coating film and the adhesion between the coating film and the substrate.

[0033] Cellulosic resins encompass linear polymers (cellulose) containing β-glucose as repeating units, and their derivatives in general. Examples of cellulose resins include methylcellulose (MC), ethylcellulose (EC), hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, carboxyethylcellulose, and nitrocellulose. Polyvinyl acetal resins encompass polymers having structural units in which continuous vinyl alcohol structural units are acetalized by an aldehyde compound, and which may have one or more of the unreacted vinyl alcohol structural units and vinyl acetate structural units, which are the unsaponified portion of the polyvinyl alcohol resin, and their derivatives (modified products, etc.). An example of a polyvinyl acetal resin is polyvinyl butyral resin (PVB), which has a structure in which polyvinyl alcohol is acetalized with butanol.

[0034] For example, from the viewpoint of suppressing the increase in residue after firing while allowing the binder resin to function more appropriately, if the total Ni paste is considered to be 100% by mass, the binder resin content (by mass) is, for example, 0.1% to 10% by mass, preferably 0.5% to 8% by mass, and more preferably 1% to 5% by mass or 1% to 3% by mass. This range is particularly preferable, for example, when producing a coating film of Ni paste using screen printing or gravure printing. Alternatively, from the viewpoint of improving the adhesion between inorganic components, the adhesion between inorganic components and the substrate, if the inorganic components contained in the Ni paste are considered to be 100 parts by mass, the binder resin content (by mass) is, for example, 0.1 parts by mass to 15 parts by mass, preferably 0.5 parts by mass to 10 parts by mass, and more preferably 1 part by mass to 5 parts by mass.

[0035] The dispersant is an organic compound that uniformly disperses inorganic components in the Ni paste, thereby suppressing aggregation. The dispersant contains a first dispersant, a second dispersant, and a third dispersant.

[0036] The first dispersant is given by the following formula (X): [ka] The compound is represented by formula (X). In formula (X), R1 is a chain hydrocarbon group having 10 to 20 carbon atoms. The chain hydrocarbon group R1 may be a linear hydrocarbon group containing a double bond (e.g., a cis double bond). As the first dispersant, for example, N-oleoyl sarcosine (hereinafter also referred to as "oleoyl sarcosine") can be preferably used. In Ni paste, the first dispersant is the total surface area (m²) of the inorganic components. 2 It is sufficient that at least 0.45 mg is contained relative to ), or 0.45 mg or more, for example, 3.5 mg or less, preferably 3 mg or less, and more preferably 2.8 mg or less. Here, the total surface area of ​​the inorganic components (m²) 2 The total surface area (m²) of the inorganic components is calculated using the BET specific surface area and content percentage (mass%) of each component contained in the inorganic components. 2 ) is the sum of the values ​​obtained by multiplying the BET specific surface area of ​​each component by its content percentage (mass %).

[0037] The second dispersant is a polyether acid and / or polycarboxylic acid. A polyether acid is, for example, a compound containing multiple ether bonds (-O-) and at least one carboxyl group. A polycarboxylic acid is, for example, a compound containing multiple carboxyl groups.

[0038] The acid value of the second dispersant is not particularly limited, but is, for example, 10 mg KOH / g to 300 mg KOH / g, preferably 20 mg KOH / g to 250 mg KOH / g, more preferably 30 mg KOH / g to 200 mg KOH / g, and even more preferably 40 mg KOH / g to 150 mg KOH / g. In this specification, "acid value" for the dispersant refers to the number of milligrams of potassium hydroxide (KOH) required to neutralize the acid contained in 1 g of the dispersant, and is the value obtained by titration using a potassium hydroxide solution in an ethanol / toluene mixed solvent. The acid value of the second dispersant can be measured, for example, by using a commercially available titration apparatus. Alternatively, the manufacturer's nominal value may be adopted. Alternatively, the acid value of the second dispersant may be a value obtained based on the chemical formula of the second dispersant and the molecular weight calculated from said chemical formula.

[0039] The second dispersant can, for example, contribute to improving the dispersibility of dielectric powders. When the total Ni paste is considered to be 100% by mass, the content of the second dispersant is, for example, 0.01% to 1.0% by mass, and preferably 0.05% to 0.8% by mass.

[0040] The third dispersant is an alkylamine. From the viewpoint of handling, the alkylamine as the third dispersant is preferably a liquid or solid at room temperature. Although not particularly limited, from the viewpoint of adsorption to barium titanate particles, the alkylamine is preferably a primary or secondary amine. The number of carbon atoms in the alkylamine is, for example, 2 or more, preferably 3 or more, and may be 22 or less, or 20 or less.

[0041] The amine value of the third dispersant is not particularly limited, but is, for example, 10 mg KOH / g to 1500 mg KOH / g, and preferably 50 mg KOH / g to 1000 mg KOH / g. In this specification, "amine value" for a dispersant refers to the number of milligrams of hydrochloric acid (HCl) required to neutralize the amine contained in 1 g of the dispersant, and is a value obtained based on the chemical formula of the third dispersant and the molecular weight calculated from said chemical formula. The amine value of the third dispersant may be obtained by measuring it using a commercially available titration device, or the manufacturer's nominal value may be adopted.

[0042] The third dispersant can, for example, contribute to improving the dispersibility of dielectric powders. When the total Ni paste is considered to be 100% by mass, the content of the third dispersant is, for example, 0.01% to 1% by mass, and preferably 0.03% to 0.8% by mass.

[0043] In Ni paste, the sum of the amine values ​​of the second dispersant and the third dispersant is A. T The sum of the acid values ​​of the second dispersant and the third dispersant, C. T The ratio (A T / C T The ratio is 1.11 to 7.50. The second dispersant is dispersant DT21, DT22, DT23, ..., DT2 n If it contains, the acid values ​​of each dispersant are AC21, AC22, AC23, ..., AC2 n The amine values ​​of each dispersant are AM21, AM22, AM23, ..., AM2 n The content (mass%) of each dispersant relative to the total Ni paste is W21, W22, W23, ..., W2 n Assume that the third dispersant is dispersant DT31, DT32, DT33, ..., DT3 m If it contains, the acid value of each dispersant is AC31, AC32, AC33, ..., AC3 m The amine values ​​of each dispersant are AM31, AM32, AM33, ..., AM3 m The content (mass%) of each dispersant relative to the total Ni paste is W31, W32, W33, ..., W3 mAssume that n and m are natural numbers less than or equal to 10 or less than or equal to 5. In this case, what is the sum A? T This is given by the following equation (1): Total value A T =Σ(AM2 n ×W2 n )+Σ(AM3 m ×W3 m )...(1) It is calculated using, Total value C T The following equation (2): Total value C T =Σ(AC2 n ×W2 n )+Σ(AC3 m ×W3 m )...(2) It is calculated using [the specified formula]. Furthermore, when a mixture of the second and third dispersants is used in the preparation of Ni paste, the mixture itself is treated as either the second or third dispersant.

[0044] The total amount of dispersant in Ni paste is equal to the total surface area of ​​the inorganic components (m²). 2 For ), at least 1.40 mg is sufficient, or it may be 1.40 mg or more, for example, 7.0 mg or less, 6.50 mg or less, 6.0 mg or less, or 5.5 mg or less.

[0045] The dispersant may include other dispersants different from the first, second, and third dispersants, insofar as the effects of the techniques disclosed herein are realized.

[0046] While not particularly limited, commercially available dispersants containing at least one of the second and third dispersants may include, for example, "ED116" and "ED404" manufactured by Kusumoto Chemical Co., Ltd., and "Floren DOPA-100" manufactured by Kyoeisha Chemical Co., Ltd. "ED116" is a mixture of a higher fatty acid and an alkylamine. In "ED116," the dispersant components are dispersed in petroleum naphtha (solvent), and the effective concentration of the components is 52% by mass. "ED404" is a mixture of a polyetheric acid and an alkylamine. In "ED404," the dispersant components are dispersed in dihydroterpineol (solvent), and the effective concentration of the components is 50% by mass. "Floren DOPA-100" is a mixture of an oligomer and a polycarboxylic acid.

[0047] In this context, the organic solvent is a component that disperses the inorganic components. It is preferable that the organic solvent is removed during the drying process in the process of forming the Ni paste's calcined film. Any organic solvent used in Ni pastes for this type of application can be used without particular limitations. While not particularly limited, examples of organic solvents include alcohol-based solvents having an -OH group, ether-based solvents having an ether bond (RO-R'), ester-based solvents having an ester bond (RC(=O)-O-R'), and hydrocarbon-based solvents composed of carbon and hydrogen atoms. For example, petroleum-based hydrocarbon solvents and terpineol-based solvents are preferably used as organic solvents. One type of organic solvent may be used alone, or two or more types may be used in appropriate combinations.

[0048] Examples of alcohol-based and ether-based solvents include terpineol, texanol, dihydroterpineol, benzyl alcohol, 3-methoxy-3-methyl-1-butanol, phenoxyethanol, 1-phenoxy-2-propanol, isoborneol, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether (butyl carbitol), propylene glycol monobutyl ether, and dipropylene glycol methyl-n-propyl ether. Examples of ester solvents include 3-methoxy-3-methyl-1-butanol acetate, 3-methoxybutyl acetate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol diacetate, cyclohexanol acetate, isobornyl acetate, carbitol acetate, ethyl diglycol acetate, butyl glycol acetate, butyl diglycol acetate, butyl cellosolve acetate, diethylene glycol monobutyl ether acetate (butyl carbitol acetate), terpineol acetate, and dihydroterpineol acetate. Examples of hydrocarbon solvents include aromatic hydrocarbon solvents such as toluene and xylene; paraffinic solvents such as normal paraffins and isoparaffins; naphthenic solvents such as monocyclic naphthenes and bicyclic naphthenes; aliphatic hydrocarbon solvents such as paraffin / naphthene mixtures and mineral spirits.

[0049] The content of organic solvents in Ni paste is not particularly limited. From the viewpoint of improving removeability during drying, the content of organic solvents when the entire Ni paste is considered as 100% by mass is, for example, 70% by mass or less, preferably 65% ​​by mass or less, and more preferably 60% by mass or less. From the viewpoint of improving the dispersibility of inorganic components and improving the coatability on the substrate, the content of organic solvents when the entire Ni paste is considered as 100% by mass is, for example, 5% by mass or more, preferably 10% by mass or more, and more preferably 20% by mass or more.

[0050] The Ni paste may contain any additives, as long as the effects of the technologies disclosed herein are not limited. Additives used in this type of Ni paste are not particularly limited. Examples of additives include antisintering agents, thickeners, plasticizers, pH adjusters, stabilizers, leveling agents, defoamers, antioxidants, preservatives, and colorants (pigments, dyes). The amount of additives in the Ni paste is not particularly limited. When the total Ni paste is considered as 100% by mass, the additive content is, for example, 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.

[0051] As described above, the Ni paste disclosed herein comprises an inorganic component, a binder resin, a dispersant, and an organic solvent. The inorganic component comprises nickel powder and dielectric powder. The dispersant is given by the following formula (X): [ka] (In the formula, R1 is a chain-like hydrocarbon group having 10 to 20 carbon atoms.) The first dispersant is represented by , the second dispersant is a polyether acid and / or polycarboxylic acid, and the third dispersant is an alkylamine. In Ni paste, the first dispersant is the total surface area (m²) of the inorganic components. 2 ) contains at least 0.45 mg. The sum of the amine values ​​of the second dispersant and the third dispersant is A. T The sum of the acid values ​​of the second dispersant and the third dispersant, C. T The ratio (A T / C T The ratio is 1.11 to 7.50. The total amount of dispersant is the total surface area (m²) of the inorganic components. 2 ) contains at least 1.40 mg.

[0052] In a Ni paste comprising an inorganic component containing nickel powder and dielectric powder, a dispersant, and an organic solvent, the dispersant includes a first dispersant shown in formula (X). The first dispersant here has the function of enhancing the dispersibility of nickel powder. The first dispersant contains an amide group, and for example, the O=CN portion (electron resonance structure portion) of the amide group can adsorb to nickel particles, thereby enhancing the dispersibility of nickel powder. Furthermore, the first dispersant is an acid amide containing a carboxyl group. This enhances the adsorption of the first dispersant to nickel particles. The dispersant further includes a second dispersant which is a polyether acid and / or polycarboxylic acid, and a third dispersant which is an alkylamine. The second and third dispersants here have the function of enhancing the dispersibility of dielectric powder. The second dispersant has a carboxyl group and adsorbs to basic sites (basic reaction sites that react with acid) of dielectric particles. The third dispersant has an amine group and adsorbs to acidic sites (acidic reaction sites that react with base) of dielectric particles. This allows the second and third dispersants to improve the dispersibility of the dielectric powder.

[0053] In Ni paste, the first dispersant is the total surface area (m²) of the inorganic components. 2 There is at least 0.45 mg of the second and third dispersants. T / C T The ratio is set to 1.11 to 7.50. The total amount of dispersant is equal to the total surface area (m²) of the inorganic components. 2 It contains at least 1.40 mg of ) relative to the amount. This makes it possible to improve the dispersibility of nickel powder and dielectric powder in Ni paste, and to suppress aggregation of nickel particles and dielectric particles. In other words, in Ni paste, it is possible to suppress aggregation of nickel particles with each other, aggregation of dielectric particles with each other, and aggregation of nickel particles and dielectric particles, thereby improving the dispersibility of each particle.

[0054] The average particle size of the nickel powder, based on SEM observation, may be 0.1 μm to 0.5 μm. Even when the nickel powder has an average particle size to which the Ni paste is applied, the effects of the technology disclosed herein are adequately realized.

[0055] The average particle size of the dielectric powder may be 5 nm to 100 nm. Even when the Ni paste contains dielectric powder having an average particle size, the effects of the technology disclosed herein are appropriately realized.

[0056] When the total inorganic components are considered to be 100% by mass, the nickel powder content may be 70% to 97% by mass. This improves the conductivity of the fired film and allows the dielectric powder to perform its function more appropriately.

[0057] When the total inorganic components are considered to be 100% by mass, the content of dielectric powder may be 3% to 30% by mass. This allows the dielectric powder to perform its function more appropriately and improves the conductivity of the fired film.

[0058] The Ni paste disclosed herein may be used to form internal electrodes of electronic components. As described above, the dispersibility of nickel powder and dielectric powder is enhanced in the Ni paste. Therefore, internal electrodes with greater uniformity can be obtained.

[0059] Electronic components can be manufactured using the Ni paste disclosed herein. The method for manufacturing the electronic component involves forming a coating film of the Ni paste disclosed herein on the surface of a substrate; and, A heat treatment is applied to the substrate and the coating to obtain a fired coating film; It includes.

[0060] Prior to or during the implementation of this manufacturing method, the Ni paste disclosed herein may be prepared. The means for preparing the Ni paste (means for preparing the Ni paste) are not particularly limited, and conventionally known means may be used as appropriate. The Ni paste can be prepared, for example, by weighing nickel powder, dielectric powder, binder resin, dispersant, organic solvent, and other additives to a predetermined content ratio (mass ratio) and homogeneously stirring and mixing them. For example, first, an organic component such as an organic solvent and binder resin is mixed to prepare a vehicle. Then, the vehicle, nickel powder, and dielectric powder are mixed and stirred. At this time, an inorganic powder slurry may be prepared in advance by dispersing inorganic powder in a dispersion medium such as an organic solvent, and this slurry may be mixed with the vehicle. Alternatively, an inorganic powder slurry may be prepared for each of the nickel powders and dielectric powders. An inorganic powder slurry may also be prepared by mixing each powder. Conventionally known mixing and stirring devices can be used for the preparation without particular limitation. Examples of such devices include ball mills, bead mills, roll mills, magnetic stirrers, planetary mixers, dispersers, high-pressure dispersers, and mortars.

[0061] Any conventionally known method may be used without particular limitation as a means for forming a Ni paste coating on the substrate surface. Examples of such means include printing methods such as screen printing, gravure printing, offset printing, and inkjet printing; spray coating methods; dip coating methods; and so on. Among these, screen printing and gravure printing are preferably used. The substrate may be, for example, a green sheet containing a dielectric (dielectric sheet). For example, in the manufacture of an MLCC, which is an electronic component, Ni paste is first applied to a dielectric sheet and dried to form a dried Ni paste film on the dielectric sheet (formation of the first laminate). Here, the first laminate comprises a dielectric sheet and a dried Ni paste film provided on the surface of the dielectric sheet. Next, a plurality of first laminates are stacked in the thickness direction of the first laminate to produce a second laminate. Here, the second laminate comprises a plurality of first laminates. Next, pressure is applied to the second laminate in the direction in which the first laminates were stacked to press the first laminates together and produce a laminated crimped body. Then, if necessary, the laminated crimped body is cut to a desired size. Next, the laminated crimped body after cutting is fired under appropriate conditions. This causes the dielectric sheet to be fired to form a dielectric layer. The dried Ni paste film is fired to form an internal electrode layer. The dielectric layer and the internal electrode layer are fired together to obtain a laminated chip. Afterward, external electrode material is applied to the sides of the laminated chip and fired to form the external electrodes. In this way, an MLCC is manufactured.

[0062] Figure 1 is a schematic cross-sectional view of MLCC1. As shown in Figure 1, MLCC1 is a chip-type capacitor constructed by alternately and integrally stacking dielectric layers 20 and internal electrode layers 30. A pair of external electrodes 40 are provided on the side surface of the stacked chip 10 including the dielectric layers 20 and internal electrode layers 30. As shown in Figure 1, the internal electrode layers 30 are alternately connected to different external electrodes 40 in the stacking order. This connects the capacitor structure including the dielectric layers 20 and the pair of internal electrode layers 30 flanking the dielectric layers 20 in parallel, constructing a small and high-capacitance MLCC1. The dielectric layers 20 are made of, for example, a dielectric material used in this type of application. The internal electrode layers 30 are fired films of Ni paste disclosed herein. The external electrodes 40 are fired films of external electrode paste used in this type of application.

[0063] The following describes test examples relating to the technology disclosed herein. However, the following description is not intended to limit the technology disclosed herein to those shown in the test examples.

[0064] [Preparation of Ni paste] <Preparing the materials> Nickel powders N1 to N3 were prepared as nickel powders. For nickel powder N1, the BET specific surface area was 3.57 m². 2 The particle size was 0.19 μm / g, the BET particle size was 0.22 μm, and the average particle size was 0.22 μm. For nickel powder N2, the BET specific surface area was 5.6 m². 2 The particle size was 0.12 μm / g, the BET particle size was 0.12 μm, and the average particle size was 0.18 μm. For nickel powder N3, the BET specific surface area was 1.68 m². 2 The particle size was / g, the BET particle size was 0.4 μm, and the average particle size based on SEM observation was 0.43 μm.

[0065] As dielectric powders, barium titanate powders BT1-BT3 and calcium zirconate titanate strontium powder SCZT were prepared. For barium titanate powder BT1, the BET specific surface area was 39 m². 2 / g, a BET particle diameter of 26 nm, and an average particle diameter of 28 nm. Regarding the barium titanate powder BT2, the BET specific surface area was 62 m 2 / g, a BET particle diameter of 16 nm, and an average particle diameter of 17 nm. Regarding the barium titanate powder BT3, the BET specific surface area was 22 m 2 / g, a BET particle diameter of 45 nm, and an average particle diameter of 53 nm. Regarding the calcium strontium zirconate titanate powder SCZT, the BET specific surface area was 18 m 2 / g, a BET particle diameter of 64 nm, and an average particle diameter of 70 nm.

[0066] Ethyl cellulose was prepared as a binder resin. Isobornyl acetate was prepared as an organic solvent. Dispersants D1 to D8 were prepared as dispersants. The components, acid values, and amine values of each dispersant are as shown in Table 1. The dispersant D1 is an example of the first dispersant in the technology disclosed herein. The dispersant D3 is an example of the second dispersant in the technology disclosed herein. The dispersant D4 and the dispersant D5 are examples of the third dispersant in the technology disclosed herein. The dispersant D6 is a mixture containing at least an example (alkylamine) of the third dispersant in the technology disclosed herein. The dispersant D7 is a mixture containing an example (polyether acid) of the second dispersant and an example (alkylamine) of the third dispersant in the technology disclosed herein. The dispersant D8 is a mixture containing at least an example (polycarboxylic acid) of the second dispersant in the technology disclosed herein.

[0067] [Table 1]

[0068] [Preparation of Ni Paste] Ni pastes containing nickel powder, dielectric powder, binder resin, dispersant, and organic solvent were prepared. First, a vehicle was prepared by mixing the organic components of the binder resin, dispersant, and organic solvent. Next, the Ni pastes for each example were prepared by mixing the vehicle with the nickel powder and dielectric powder and stirring. For each example of Ni paste, the type of nickel powder, the type of dielectric powder, and the content percentage (mass%) of each component in the Ni paste are shown in the corresponding columns of Tables 2 and 3. Here, in Tables 2 and 3, the content percentage of the organic solvent is not indicated for each component. The content percentage of the organic solvent has been adjusted so that when the sum of the content percentages of the components listed in the table is added to the content percentage of the organic solvent, it equals 100 mass%. In addition, the "Amount of Dispersant A (mg / m³)" in the table is also shown. 2 In the column, the amount of dispersant A relative to the total surface area of ​​the inorganic components in each example (mg / m²) 2 ) is indicated. Note that in this test example, only D1 of the above-mentioned dispersants is classified as dispersant A. Of the above-mentioned dispersants, D2 to D8 are classified as dispersant B or dispersant C in the table. For example, if the Ni paste contains one of the dispersants D2 to D8, that dispersant is classified as dispersant B (see, for example, Examples 12 to 14). If the Ni paste contains two of the dispersants D2 to D8, one of the two is classified as dispersant B and the other as dispersant C (see, for example, Examples 1 to 11). Furthermore, in the table, the ratio (A) is indicated in each example. BC / C BC The ratio (A) is shown. BC / C BC ) is the sum of the amine values ​​of the dispersant listed in the "Dispersant B" column of the table and the amine values ​​of the dispersant listed in the "Dispersant C" column of the table. BC The sum of the acid value of the dispersant listed in the "Dispersant B" column of the same table and the acid value of the dispersant listed in the "Dispersant C" column of the same table, C. BC This is the ratio (A). BC / C BC The calculation of ) requires the ratio (A T / C T), the above formula (1) and the above formula (2) were used. Further, in the "Total amount of dispersant (mg / m 2 )" column in the table, for each example, the total amount of dispersant relative to the total surface area of the inorganic component (mg / m 2 ) is indicated.

[0069] [Table 2]

[0070] [Table 3]

[0071] <Evaluation of separability of Ni paste> The Ni paste of each example was left to stand for 30 days in an environment at 25°C. With respect to the Ni paste after standing, the presence or absence of floating of dielectric powder was visually observed. An example in which no floating of dielectric powder was observed was evaluated as no separation (pass), and an example in which floating of dielectric powder was observed was evaluated as separation present (fail). Note that FIG. 2 shows an example in which no floating of dielectric powder was observed (pass example). FIG. 3 shows an example in which floating of dielectric powder was observed (fail example).

[0072] <Evaluation of dispersibility of Ni paste> A vehicle was added to each Ni paste so that the inorganic component content was 5% by mass. A mixture of ethylcellulose and dihydroterpineol was used as the vehicle. The mass ratio of each component in the vehicle (ethylcellulose:dihydroterpineol) was 20:80. The Ni paste with the added vehicle was coated onto a glass substrate using an applicator (gap 5 μm) and dried at 100°C for 5 minutes to form a coating film. The surface roughness of the coating film of the Ni paste coated on the glass substrate was then measured to evaluate the dispersibility of the inorganic component. Specifically, the surface of the coating film was observed with a laser microscope (Keyence Corporation, "VK-X1050") and the surface roughness (maximum height Sz) was measured. Surface roughness was measured on three randomly selected 2 mm square observation fields on the coating film. A surface roughness (maximum height Sz) of 15 μm or less was evaluated as having good dispersibility (pass), and a surface roughness (maximum height Sz) exceeding 15 μm was evaluated as not having good dispersibility (fail).

[0073] <Overall Rating> Each Ni paste sample was evaluated based on the following criteria. "E"... It was evaluated as "passing" in both the separability assessment and the dispersion assessment. "P"... Failed in either the separability assessment or the divergence assessment. It is expected that a more uniform fired film can be obtained by using the Ni paste that was evaluated as "E".

[0074] From the results shown in Table 2 and Table 3, it was found that in Examples 1 to 19, the nickel powder and the dielectric powder are highly dispersed, and the Ni paste can enhance the uniformity of the fired film. Examples 1 to 19 are Ni pastes comprising an inorganic component containing nickel powder and dielectric powder, a binder resin, a dispersant, and an organic solvent. The dispersant includes a first dispersant which is oleoyl sarcosine, one of the compounds having the structure represented by formula (X), a second dispersant which is a polyether acid and / or a polycarboxylic acid, and a third dispersant which is an alkylamine. The first dispersant in the Ni paste is at least 0.45 mg relative to the total surface area (m 2 ) of the inorganic component. The sum A of the amine value of the second dispersant and the amine value of the third dispersant T and the sum C of the acid value of the second dispersant and the acid value of the third dispersant T T / C T ) is 1.11 to 7.50. The total amount of the dispersant is at least 1.40 mg relative to the total surface area (m 2 ) of the inorganic component.

[0075] The technology disclosed herein has been described in detail above, but these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the embodiments exemplified above.

[0076] The technology disclosed herein encompasses the following modes. Item 1: An inorganic component containing nickel powder and dielectric powder, a binder resin, a dispersant, an organic solvent, A Ni paste comprising wherein the dispersant is represented by the following formula (X): [Chemical Formula] (In the formula, R1 is a chain hydrocarbon group having 10 to 20 carbon atoms.) a first dispersant represented by​ a second dispersant that is a polyether acid and / or a polycarboxylic acid, a third dispersant that is an alkylamine, , the first dispersant in the Ni paste is present in an amount of at least 0.45 mg relative to the total surface area (m 2 ) of the inorganic component, the sum A of the amine value of the second dispersant and the amine value of the third dispersant T and the sum C of the acid value of the second dispersant and the acid value of the third dispersant T has a ratio (A T / C T ) of 1.11 to 7.50, the total amount of the dispersants is at least 1.40 mg relative to the total surface area (m 2 ) of the inorganic component, Ni paste. Item 2: The average particle diameter of the nickel powder based on electron microscope observation is 0.1 μm to 0.5 μm, The Ni paste according to Item 1. Item 3: The average particle diameter of the dielectric powder based on electron microscope observation is 5 nm to 100 nm, The Ni paste according to Item 1 or 2. Item 4: When the total amount of the inorganic component is taken as 100 mass%, the content of the nickel powder is 70 mass% to 97 mass%, The Ni paste according to any one of Items 1 to 3. Item 5: When the total amount of the inorganic component is taken as 100 mass%, the content of the dielectric powder is 3 mass% to 30 mass%, The Ni paste according to any one of Items 1 to 4. Item 6: Used for forming internal electrodes of electronic components, The Ni paste according to any one of Items 1 to 5. Item 7: forming a coating film of the Ni paste according to any one of Items 1 to 6 on the surface of a base material; and, The substrate and the coating film are subjected to heat treatment to obtain a fired coating film; to include, Manufacturing methods for electronic components. [Explanation of symbols]

[0077] 1 MLCC 10 stacked chips 20 Dielectric layer 30 Internal electrode layer 40 External electrode

Claims

1. An inorganic component containing nickel powder and dielectric powder, Binder resin and Dispersant and Organic solvents and Ni paste containing, The aforementioned dispersant is The following equation (X): 【Chemistry 1】 (In the formula, R 1 (This refers to a chain-like hydrocarbon group with 10 to 20 carbon atoms.) The first dispersant shown, A second dispersant which is a polyetheric acid and / or polycarboxylic acid, A third dispersant which is an alkylamine, Includes, The first dispersant in the Ni paste has a total surface area (m²) of the inorganic components. 2 ) contains at least 0.45 mg, The sum of the amine values ​​of the second dispersant and the third dispersant is A. T The sum of the acid values ​​of the second dispersant and the third dispersant, C. T The ratio (A T / C T ) ranges from 1.11 to 7.50, The total amount of the dispersant is the total surface area (m²) of the inorganic components. 2 ) contains at least 1.40 mg, Ni paste.

2. The average particle size of the nickel powder, based on electron microscope observation, is 0.1 μm to 0.5 μm. Ni paste according to claim 1.

3. Based on electron microscope observation, the average particle size of the dielectric powder is 5 nm to 100 nm. Ni paste according to claim 1.

4. When the total amount of the inorganic components is considered to be 100% by mass, the content of the nickel powder is 70% by mass to 97% by mass. Ni paste according to claim 1.

5. When the total amount of the inorganic components is considered to be 100% by mass, the content of the dielectric powder is 3% to 30% by mass. Ni paste according to claim 4.

6. Used in the formation of internal electrodes of electronic components, Ni paste according to claim 1.

7. Forming a coating film of Ni paste according to any one of claims 1 to 6 on the surface of the substrate; and, The substrate and the coating film are subjected to heat treatment to obtain a fired coating film; to include, Manufacturing methods for electronic components.

Citation Information

Patent Citations

  • Conductive paste for photogravure used for multilayer ceramic capacitor internal electrode

    JP2012174797A

  • Manufacturing method of dispersible nickel fine particle slurry

    JP2014088603A

  • Production method of conductive paste and conductive paste obtained by the method

    JP2016031912A

  • Electroconductive paste, electronic component, and laminated ceramic capacitor

    JP2025081376A

  • Conductive paste for internal electrodes of multilayer ceramic capacitors

    JP4238575B2